The Benefits of the Outsourcing Strategy as Perceived by the Industrial Companies in Jordan (Global Journal of Management and Business Research, 2016)
This paper seeks to explore the benefits gained from the outsourcing strategy implemented by industrial companies in Jordan in terms of cost reduction, focus on core competencies, access to specialized resources, quality improvement, and the perceived benefits. This was achieved by testing hypotheses based on the main objectives of the study. The population of the study consisted of all of the manufacturing companies located at the Sahab industrial estate, Jordan, while the respondents are made up of those who occupy managerial positions in the aforementioned companies. A survey questionnaire was developed, relying mainly on the study of Gewald et al. (2004), with contributions from the studies of Anderson (1997) and Kotabe et al. (2008). The researchers distributed 130 questionnaires but only 122 were retrieved, out of which 114 were considered valid for statistical treatment.
Keywords: outsourcing strategy; industrial companies; Jordan